Activity Based Costing Method For Determining Ticket Fare on Inter-State Bus Transportation - admin, Benny Handoko B42111009 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This study aims to analyze the methods used by Perum Damri Company in calculating the Cost of Goods Sold (COGS). Applications of both methods, Traditional and Activity Based Costing System (ABC), were the focuses of this study. The calculation of COGS comes to be important since it serves as a basis for setting the fare of offered products. The result of this study is expected to set appropriate fare-rates that can be useful to both company and consumers. The company, therefore, can provide a better service and satisfy consumers. The object of this study is Perum Damri Pontianak, a company which provides an international public transportation service in West Kalimantan, Indonesia. The sample analysed in this study was the companyâ€™s annual financial report of 2014. The results of analyses of both Traditional and ABC methods then were then compared with each other. The result of the research shows that the allocation of costs in determining the Cost of Goods Sold is more accurate when using Activity Based Costing. It is because specific costs are imposed on activity-based products, and the resources that are consumed by the products as well as the use of more than one cost driver. Therefore, the fare established by the company is more accurate. Â  Keywords: Activity Based Costing (ABC), Cost Of Goods Sold (COGS), Unit Cost, Analysis Cost